Declaración de testigos en la investigación policial y el valor probatorio en el delito de robo agravado, Arequipa 2018 - Mendoza Arredondo, Omar Tiberio (2017)
The life of a human being and its beginning as such is an uncertain title, as there is no exact and scientific determination to help determine such a title, so, there are concepts that seem fundamental to this legal determination, with the purpose of look for legal solutions to make possible its application at national level, the same one that unfortunately has had a slow advance in its development. In this regard research has as its fundamental theme the determination of a fundamental right which is the legal recognition of human life as such in the Peruvian legislation in force in the light of supranational jurisprudence, based on the different currents figures international legal, thus questioning the customs paradigm of the various studies obtained in the local area clinging to custom and tradition, even if these have become inoperative contradictory or obsolete, in order to change and change to adapt to the new circumstances that we face daily in the current democratic and globalized society where the issues are continually debated, all the rights that are applied in the supranational jurisprudence.